Options for local financing in urban agriculture - Egyir, I.S.; Cofie, Olufunke O.; Dubbeling, Marielle (2014)
Access to debt financing (credit) is crucial to the development of urban agricultural production, processing and marketing activities. This chapter is based on a 2009 study 1 carried out in Accra to assess the practices of institutions and programs that could finance urban agriculture as well as the existing bottlenecks and opportunities in financing. Information is based on surveys involving 179 respondents sampled from financial institutions; urban farmers (not limited to vegetable farmers), traders and processors; literature reviews, stakeholder mapping; focus group discussions; key informant interviews; and a validation workshop.